Pressure-Driven Thermal Slip Flow in the Elliptical Channel with Radial Oscillatory Wall - Nattawan Chuchalerm; Benchawan Wiwatanapataphee; Wannika Sawangtong (Journal of Applied Mathematics)
This paper is aimed at presenting thermal slip flow driven by oscillatory pressure gradient in a deformable microchannel of elliptic cross-section. The fully developed flow of Newtonian fluid is considered, and Navier slip is applied on the boundary. The boundary value problem is formulated and applied to the coronary blood flow-heat transfer phenomenon during thermotherapy treatment. Its semianalytical solutions of velocity and temperature fields are carried out by the Ritz method. The effects of oscillatory wall and slip length on velocity and temperature fields of blood are investigated.